2004
DOI: 10.1074/jbc.m400887200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Splicing of a Pyrococcus abyssi Intein with a C-terminal Glutamine

Abstract: Protein splicing involves the excision of an intervening polypeptide sequence, the intein, from a precursor protein and the concomitant ligation of the flanking polypeptides, the exteins, by a peptide bond. Most reported inteins have a C-terminal asparagine residue, and it has been shown that cyclization of this residue is coupled to peptide bond cleavage between the intein and C-extein. We show that the intein interrupting the DNA polymerase II DP2 subunit in Pyrococcus abyssi, which has a C-terminal glutamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 34 publications
4
65
0
Order By: Relevance
“…However, our results showed that the N-intein linked to the N-extein could be as short as 11 aa and that a major portion (M-intein) of the intein could be unlinked from both exteins. In addition, other studies have shown that even the few conserved junction residues can be absent (35)(36)(37)(38). Taken together, these findings could suggest the possible existence of highly derived inteins that show no obvious sequence similarity to known self-splicing inteins.…”
Section: Discussionmentioning
confidence: 75%
“…However, our results showed that the N-intein linked to the N-extein could be as short as 11 aa and that a major portion (M-intein) of the intein could be unlinked from both exteins. In addition, other studies have shown that even the few conserved junction residues can be absent (35)(36)(37)(38). Taken together, these findings could suggest the possible existence of highly derived inteins that show no obvious sequence similarity to known self-splicing inteins.…”
Section: Discussionmentioning
confidence: 75%
“…Asp and Gln can undergo similar cyclization reactions. 6,7,[9][10][11] The intein penultimate His assists Asn cyclization. 6,7 A native peptide bond is formed between the exteins (VI) after a spontaneous [S/O]-N acyl shift.…”
Section: Introductionmentioning
confidence: 99%
“…This led the authors to hypothesize that the newly formed amino group at the intein N-terminus in the branched intermediate cleaves the C-terminal splice junction (17). This is inconsistent with the Pab PolII intein data yielding C-terminal cleavage in the absence of N-terminal cleavage (18). Another possibility is that the Cterminal scissile bond is activated for cleavage by an oxygen nucleophile (Asp) and is thus very susceptible to hydrolysis.…”
Section: Inteins Ending In Gln or Aspmentioning
confidence: 96%
“…Asp and Gln can undergo similar rearrangements to Asn that would result in peptide bond cleavage. C-terminal cleavage in the Gln containing Pyrococcus abyssi (Pab) PolII intein was facilitated by the intein penultimate His (18). A C-terminal aminoglutarimide has not been observed, possibly because of instability or because another mechanism is being utilized (17).…”
Section: Inteins Ending In Gln or Aspmentioning
confidence: 99%
See 1 more Smart Citation